Feed handling practices, aflatoxin awareness and children's milk consumption in the Sidama region of southern Ethiopia - Anato, Anchamo; Headey, Derek D.; Hirvonen, Kalle; Pokharel, Ashish; Tessema, Masresha; Wu, Felicia; Baye, Kaleab (Elsevier, 2024)
Consumption of milk is linked to improved nutrient intake and reduced risk of child malnutrition in low and middle-income countries. However, these benefits are contingent on the safety and quality of the milk. Milk consumption may alleviate the widespread risk of malnutrition in rural Ethiopia, but milk-borne contaminants may also compromise child health. We aimed to: i) identify the types of dairy feeds used, their storage conditions, and potential risk of aflatoxin contamination; ii) assess stakeholders' knowledge about aflatoxin contamination along the value chain; and iii) assess parental practices on feeding milk to infants and young children. This qualitative study was conducted in the Sidama region, southern Ethiopia. In-depth interviews (n = 12) and key-informant interviews (n = 18) were conducted with actors along the dairy value chain. Focus-group discussions were conducted with farmers (9FGD/n = 129) and child caregivers (9FGD/n = 122). Study participants were selected to represent a rural-urban gradient, as well as low- and high- dairy cow holdings. We found that while animal-feed processors and their distribution agents had relatively good knowledge about aflatoxin, farmers and retailers did not. Feed storage conditions were poor. Many respondents linked moldy feeds to animal health but not to human health. Farmers' feed choice was influenced by cost, seasonality, and herd size. Small-holding farmers had limited access to commercial feed. Children's consumption of milk was limited to skim milk, as butter was extracted and sold for income. The high cost of dairy products also led some parents to dilute skim milk with water before feeding children, compromising the nutritional value and safety of the milk. Our findings underscore the need to address the gaps in aflatoxin and food safety knowledge, improve storage conditions, and ensure the availability of quality feed to increase the sector's productivity, but most importantly to protect consumers' health and well-being, especially infants and young children.